Guerilla art (London, UK Laurence King, 2009)
"This book and DVD package features profiles of and interviews with the most influential street artists including Banksy, os gemeos, Invader, Barnstormers, WK Interact, Zevs and Andre. Street art pioneers Futura, Ramm:ell:zee and Blek Le Rat discuss their own work, and how street art has become a recognized art form born out of the days of subway train graffiti, spraypainting and tagging. The book also introduces Agnes B and other behind-the-scenes players of this new art movement." "Filmed in New York, London, Paris, Sao Paulo and Tokyo, the accompanying documentary shows the artists' street savvy survival tactics and their work in action: Zevs practising his 'Visual Attacks' on advertising billboards, Blek le Rat sticking up outsized stencils, os gemeos painting their lyrical, folklore-inspired murals and Invader putting up his unique mosaic wall-tile images."
Copyright 2009 Urban Canyons Ltd.
Keywords: Street art; Graffiti